Optimization of inkjetted electrodes using water-based silver nanoink - Joseph, Claire M.; Dutta, Joydeep; Hornyak, Louis; Chanchana Thanachayanont; ADB-Japan Scholarship Program (ADB-JSP) (Pathum Thani : Asian Institute of Technology, 2011)
Inkjet printing of nanoparticles is practically gammg momentum to revolutionize the emerging nanotechnology. An infinite potential applications lead to flexible devices, remarkably no waste process, low-cost gadgets and novel printed products unimaginable in the next decades. In this study, an aqueous-based silver nanoparticle ink with 5% metal loading was developed to fabricate electrodes intended for gas sensing application. The metallic nanoink was optimized to attain the most conductive electrodes after heat treatment. It was then printed on alumina substrates using a customized inkjet printer followed by nickel electroplating. Critical inkjet parameters such as substrate temperature and number of ink deposition during printing were considered to eliminate unwanted deposits on undesignated areas. The electrodes were designed using an interdigitated array pattern with the goal of reducing the inter-electrode distance to less than 1 mm. The inkjetted silver-based electrodes with inter-electrode gaps of - 0.5 mm and - 0.2 mm with - 0.15 mm line thickness were evaluated for gas sensor performance. Furthermore, they were used to study the effects and influence on the overall gas sensing characteristics and properties.
Thesis (M. Sc.) - Asian Institute of Technology, 2011
A thesis submitted in pa11ial fulfiHment of the requirements for the degree of Master of Science in Microelectronics and Embedded System, School of Engineering and Technology
Keywords: Nanoparticles; Ink-jet printing